Testing Breadth and Depth of Vocabulary Knowledge and Their Relationship with Vocabulary Size of EFL Students - Ismi Narulita Firda; Intan Azkiyah; Albiansyah (JET (Journal of English Teaching), 2021)
Abstract Testing the breadth and depth of vocabulary knowledge is needed to see its effect on the vocabulary size of EFL students. The study aims to know at the relationship between the breadth and depth of vocabulary knowledge and the vocabulary size of EFL students. This research was conducted in the 8th grade of Trimulia Junior High School Jakarta. This research uses a correlational research design. The sample was 51 EFL learners. The Vocabulary Level Test (VLT) and the Words Associates Test (WAT) were administered in this study. The scores were presented with descriptive statistics for two tests of the breadth and depth of vocabulary knowledge. The results showed that the breadth and depth of the vocabulary knowledge test had a negative correlation with the L2 vocabulary size of EFL students. Using Statistic Product moment, the correlation coefficients found at 0.01 for the breadth and 0.11 for depth is included in the very weak category. So, there is a very weak correlation between the tests of breadth and deep vocabulary knowledge and the size of students' vocabulary. Keywords: breadth, depth, vocabulary knowledge, vocabulary sizes